1,5-Bis(4-bromophenyl)-3-phenylpentane-1,5-dione - Li, Kao-Zhen (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(23)H(18)Br(2)O(2), contains two independent molecules with slightly different conformations. In the absence of classical intermolecular interactions, the crystal packing is stabilized by van der Waals forces.